Use of real-world data to study health services utilisation and comorbidities in long-term breast cancer survivors (the SURBCAN study): study protocol for a longitudinal population-based cohort study - Xavier Castells; Beatriz Poblador-Plou; Alexandra Prados-Torres; Maria Sala; Javier Gorricho; Anna Jansana; Isabel Del Cura; Teresa Sanz Cuesta; A Gimeno Miguel; Manuela Lanzuela; Berta Ibañez; Ibai Tamayo; et al. (BMJ Open)
Introduction Breast cancer has become a chronic disease due to survival improvement and the need to monitor the side effects of treatment and the disease itself. The aim of the SURBCAN study is to describe comorbidity, healthcare services use and adherence to preventive recommendations in long-term breast cancer survivors and to compare them with those in women without this diagnosis in order to improve and adapt the care response to this group of survivors.Methods and analysis Population-based retrospective cohort study using real-world data from cancer registries and linked electronic medical records in five Spanish regions. Long-term breast cancer survivors diagnosed between 2000 and 2006 will be identified and matched by age and administrative health area with women without this diagnosis. Sociodemographic and clinical variables including comorbidities and variables on the use of health services between 2012 and 2016 will be obtained from databases in primary and hospital care. Health services use will be assessed through the annual number of visits to primary care professionals and to specialists and through annual imaging and laboratory tests. Factors associated with healthcare utilisation and comorbidities will be analysed using multilevel logistic regression models. Recruitment started in December 2018.Ethics and dissemination This study was approved by the Ethics Committee of Parc de Salut Mar. The results of the study will be published in a peer-reviewed journal and will be presented at national and international scientific conferences and at patient associations.Trial registration number This protocol is registered in Clinical Trials.gov (identifier: NCT03846999).